Curvilinear association between waist-to-height ratio and cardiorespiratory fitness: a cross-sectional study based on nationwide data from Chinese children and adolescents - Jiehao Dong; Pengwei Song; Zhen Zhang; Jia Zhang (BMC, 2024)
Abstract Background Waist-to-height ratio (WHtR) is considered an important summary indicator for assessing the health of children and adolescents. However, there are fewer studies addressing the association between WHtR and cardiorespiratory fitness (CRF). Deriving an optimal WHtR would play an important role in promoting CRF in children and adolescents. Our aim was to analyze the association between WHtR and CRF and determine the optimal value of WHtR. Methods In this study, 37,081 (19,125 boys, 51.6%) children and adolescents aged 7-18 years in five regions of China were tested for WHtR and 20-m shuttle run test (20 m SRT). One-way ANOVA was used to compare maximum oxygen uptake (VO2max) among children and adolescents with different WHtRs and effect sizes were used to analyze differences between groups. Curvilinear regression was used to analyse the curvilinear relationship that exists between WHtR and VO2max. Results In Chinese children and adolescents, the WHtR of boys was higher than that of girls by 0.01, and the difference was statistically significant (P < 0.001). Overall, in the age groups of 7-9, 10-12, 13-15, and 16-18 years old, the differences in VO2max comparisons between different WHtR groups were statistically significant (P < 0.001). In Chinese children and adolescents in the age groups of 7-9, 10-12, 13-15, and 16-18 years old, VO2max levels were highest when the WHtR was 0.34, 0.32, 0.39, and 0.41, respectively. Conclusions There is a curvilinear association between WHtR and CRF in Chinese children and adolescents. Both lower and higher WHtR led to a decrease in VO2max in children and adolescents.